Preparation of powder coatings on the surface of steel balls by mechanochemical synthesis - Rakhadilov, B.K.; Buitkenov, D.B.; Sagdoldina, Zh.B.; Zhurerova, L.G.; Wieleba, W. (KU Publ., 2020)
This work presents the results of the study of tribological and corrosion properties of powder coatings based on VN, TiN, SiC and Cr2N obtained by mechanochemical synthesis on the surface of steel balls ShKh15. The idea of this method is using the impact energy of moving balls to apply coatings on metal surfaces. Based on the conducted research, it was proved using the method of mechanochemical synthesis possible to obtain a coating of VN, TiN, SiC, and Cr2N on the surface of steel balls. The optimal parameters for coating were chosen: amplitude of the oscillation 3.5 mm; frequency of the oscillation 50 Hz; volume of filling of the chamber 50 %, the diameter of the ball 6 mm; ratio mass of the powder to the mass of the balls mp:mb=1:30, processing time by mechanochemical synthesis is 1 hour. It is established that the change in the characteristics of coatings directly depends on the stiffness and physical and mechanical properties of the source material (substrate) and surface roughness. The results of the tribological study showed that a wear-resistant coating was formed on the surface of the steel balls.
Механохимиялық синтез əдісімен болат шарлардың бетіне ұнтақ жабындарын алу
Получение порошковых покрытий на поверхности стальных шаров методом механохимического синтеза
Keywords: mechanochemical synthesis; steel ShKh15; coating; coefficient of friction; wear resistance; corrosion; vibration stand; bearing